Core-shell structure functional fiber composite material based on frequency-controllable alternating electric field and preparation method thereof

By using frequency controllable alternating electric field technology in fiber composite production, the inorganic powder material is closely combined with the fiber substrate, and the problems of complex process and unstable performance in the existing technology are solved, achieving high efficiency, controllability and environmental protection preparation of composite materials.

CN119433969APending Publication Date: 2025-02-14DONGHUA UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411451797.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The production process of existing fiber composite materials is complex, and relies on traditional solvent systems and heat treatment steps, resulting in poor structural controllability and performance stability, poor universality of the preparation process, high production costs and unfriendly environment.

Method used

Using a frequency-controllable alternating electric field method, the inorganic non-metallic powder material is uniformly dispersed on the surface of the porous fiber substrate material, and an alternating electric field is applied in the alternating electric field environment to achieve the close bond between the functional powder material and the fiber substrate. , forming a core-shell structure functional fiber composite material.

Benefits of technology

It improves the preparation efficiency and production controllability of materials, realizes high-performance and environmentally friendly composite materials, solves the problems of structural stability and performance stability, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433969A_ABST
    Figure CN119433969A_ABST
Patent Text Reader

Abstract

The invention discloses a core-shell structure functional fiber composite material based on a frequency-controllable alternating electric field and a preparation method thereof. The problems that a conventional functional fiber composite material is poor in structural controllability and performance stability, poor in preparation technology universality, complex in technological process, high in production cost, not environmentally friendly and the like are mainly solved. The invention provides a preparation method of a core-shell structure functional fiber composite material based on a frequency-controllable alternating electric field, which induces charge transfer and redistribution between an inorganic functional powder material and a porous fiber substrate and charge polarization of the powder material through interaction with very low frequency electromagnetic waves generated by the alternating electric field. And under the driving of coulombic force, the powder material is assisted to quickly enter a porous fiber substrate bulk phase structure. The prepared functional fiber composite material can be applied to acoustic systems and thermal management systems.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite fiber materials, and in particular to a core-shell structure functional fiber composite material based on a frequency-controllable alternating electric field and a preparation method thereof. Background Art

[0002] High-performance fibers and their composite materials occupy a core position in the new material technology and industrial revolution, and their applications cover key areas such as aerospace, rail transportation, new energy, health industry and infrastructure construction. The functional requirements of these materials - including electrical conductivity, thermal conductivity, energy storage and catalytic performance - vary according to different application fields. Fiber composite materials are composed of functional inorganic powder materials and porous fiber base materials. They not only inherit the advantages of each component, but also achieve performance that exceeds that of a single material through synergistic effects.

[0003] However, the existing fiber composite material production process is complicated, often involving fiber structure design and molding, interface modification and functional enhancement. At present, the commonly used composite methods of fiber and functional powder include hot roll forming (CN115257087A), adhesive encapsulation (CN117777666A, CN110922095A) and in-situ wet chemical synthesis (CN118186753A) and other strategies. These methods usually rely on impregnation, spraying or brushing to composite the functional powder with the fiber substrate, and require a heat treatment step to remove the solvent. These steps not only increase the complexity of production, but also due to the use of liquid solvents, the functional powder is prone to local agglomeration and uneven distribution, resulting in the functional elements of the final product being easy to pulverize and fall off, reducing the structural controllability and performance stability of the material. In addition, the existing technology has poor universality, and the functionalization requirements of specific application fields often require the redesign of the preparation process. These limitations make it difficult to meet the development requirements of green energy saving and circular economy.

[0004] Therefore, the development of a composite fiber material that not only ensures structural stability but also has excellent performance, as well as a new composite fiber material preparation method that does not rely on traditional solvent systems and heat treatment steps, has become a key issue that needs to be solved in this field. This new method will greatly improve the preparation efficiency and production controllability of the material, and provide high-performance, environmentally friendly solutions for applications in multiple fields. Summary of the invention

[0005] In order to overcome the shortcomings of the background technology, the present invention provides a method for preparing a core-shell structured functional fiber composite material based on a frequency-controllable alternating electric field, which mainly solves the problems of poor structural controllability and performance stability of conventional functional fiber composite materials, poor universality of preparation process, complex process flow, high production cost, and environmental unfriendliness.

[0006] The technical solution of the present invention is: A method for preparing a core-shell structure functional fiber composite material based on a frequency-controllable alternating electric field comprises the following steps: Step 1: Evenly dispersing the inorganic non-metallic powder material on the surface of a porous fiber base material having a suitable pore structure; Step 2: Place the sample in an alternating electric field environment and apply the alternating electric field for 10 seconds to 10 minutes to achieve a close bond between the functional inorganic non-metallic powder material and the fiber substrate, and finally obtain a functional fiber composite material.

[0007] The inorganic non-metallic powder material includes one or more of nano silicon dioxide, aluminum oxide, silicon carbide, iron oxide, and phase change material.

[0008] In the step 2, the operating frequency of the alternating electric field is 50-1 kHz, and the alternating voltage ranges from 5000 to 20000 volts.

[0009] The functional inorganic non-metallic powder material is loaded in the porous fiber substrate pore structure, and the loading amount thereof is 0.1 wt.% to 70 wt.%.

[0010] The particle size range of the functional inorganic non-metallic powder material is within 1 mm.

[0011] The particle size range of the functional inorganic non-metallic powder material is within 300 microns.

[0012] The porous fiber base material is fiber felt.

[0013] The porous fiber base material is at least one of carbon fiber felt, glass fiber felt, basalt fiber felt, pre-oxidized fiber felt, ceramic fiber felt, and blended chemical fiber felt.

[0014] The density of the porous fiber base material is 80-300 kg / m 3 .

[0015] The thickness of the porous fiber base material is 0.5-5 mm.

[0016] A core-shell structure functional fiber composite material based on a frequency-controllable alternating electric field, characterized in that it is composed of functional inorganic non-metallic powder and porous fiber material; the functional inorganic non-metallic powder material includes one or more of nano-silicon dioxide, aluminum oxide, silicon carbide, iron oxide, and phase change material.

[0017] The beneficial effects of the present invention are as follows: the present invention provides a method for preparing a core-shell structure functional fiber composite material based on a frequency-controllable alternating electric field, which induces charge transfer and redistribution between the inorganic functional powder material and the porous fiber substrate, as well as charge polarization of the powder material through interaction with the very low frequency electromagnetic waves generated by the alternating electric field. Driven by the Coulomb force, the powder material is assisted to quickly enter the bulk structure of the porous fiber substrate, and based on the strong Coulomb interaction, the effective combination between the functional inorganic powder material and the porous fiber substrate and the structural and functional integration of the composite material are achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a schematic diagram of the experimental process of the present invention.

[0019] Figure 2 This is the XRD of the functional fiber composite material prepared in Example 1-2 of the present invention.

[0020] Figure 3 This is the SEM of the functional fiber composite material prepared in Example 1-2 of the present invention.

[0021] Figure 4 This is the EDS of the functional fiber composite material prepared in Example 1 of the present invention.

[0022] Figure 5 This is the EDS of the functional fiber composite material prepared in Example 2 of the present invention.

[0023] Figure 6 The microwave absorption performance of the functional fiber composite material prepared in Example 1 of the present invention is analyzed, wherein Figure 6 (a) is the complex dielectric constant of silicon carbide glass fiber composite material in X-band, Figure 6 (b) is the dielectric loss of silicon carbide glass fiber composite material in X-band, Figure 6 (c) is the reflection loss of silicon carbide glass fiber composite material, Figure 6 (d) is the attenuation coefficient α of silicon carbide glass fiber composite material.

[0024] Figure 7 This is a thermal insulation performance test of the functional fiber composite material prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0025] The present invention is further described below in conjunction with the accompanying drawings: as shown in the figure, a method for preparing a core-shell structure functional fiber composite material based on a frequency-controllable alternating electric field comprises the following steps: step one, uniformly dispersing an inorganic non-metallic powder material on the surface of a porous fiber base material having a suitable pore structure; step two, placing the sample in an alternating electric field environment, and applying an alternating electric field for 10 seconds to 10 minutes to achieve a close bond between the functional inorganic non-metallic powder material and the fiber base, and finally obtaining a functional fiber composite material.

[0026] Through the interaction with the very low frequency electromagnetic waves generated by the alternating electric field, charge transfer and distributed polarization are induced between the inorganic non-metallic powder material and the porous fiber substrate. Driven by the Coulomb force, the inorganic non-metallic powder material quickly enters the bulk structure of the porous fiber substrate and is tightly combined with the porous fiber substrate to form a core-shell structure. There is a Coulomb interaction between the functional unit and the porous fiber substrate, which inhibits the shedding of the functional powder structure and ensures the stability of the composite material structure.

[0027] The inorganic non-metallic powder material includes one or more of nano silicon dioxide, aluminum oxide, silicon carbide, iron oxide, and phase change material.

[0028] The phase change material mentioned here includes at least one of sodium bicarbonate, pseudo-boehmite, ammonium aluminum sulfate dodecahydrate, magnesite, calcium sulfate dihydrate, potassium carbonate, and magnesium hydroxide.

[0029] In the step 2, the operating frequency of the alternating electric field is 50-1 kHz, and the alternating voltage ranges from 5000 to 20000 volts.

[0030] The functional inorganic non-metallic powder material is loaded in the porous fiber substrate pore structure, and the loading amount thereof is 0.1 wt.% to 70 wt.%.

[0031] The particle size range of the functional inorganic non-metallic powder material is within 1 mm.

[0032] The particle size range of the functional inorganic non-metallic powder material is within 300 microns.

[0033] The porous fiber base material is fiber felt.

[0034] The porous fiber base material is at least one of carbon fiber felt, glass fiber felt, basalt fiber felt, pre-oxidized fiber felt, ceramic fiber felt, and blended chemical fiber felt.

[0035] The density of the porous fiber base material is 20-1000 kg / m 3 , preferably 50-800kg / m 3 , preferably 80~300 kg / m3 .

[0036] The thickness of the porous fiber base material is 0.1-20 mm, preferably 0.3-10 mm, preferably 0.5-5 mm.

[0037] Example 1 In this embodiment, the functional nano silicon carbide inorganic powder material is placed in an oven and dried at 120°C for 1 hour to ensure that the material is fully dried. Use a fiber cutter to cut the glass fiber mat into 150mm*150mm, then weigh the required loading amount of 20wt.% of nano silicon carbide inorganic powder material, and evenly disperse the nano silicon carbide powder on the porous fiber base material; place the porous fiber base material loaded with the above-mentioned nano silicon carbide inorganic powder material in an alternating electric field environment, wherein the voltage of the alternating electric field is set to 5kV and the frequency is set to 50Hz. Very low frequency electromagnetic waves are generated by the alternating electric field, and the sample is ensured to be fully processed, and finally a functional fiber composite material sample 1 is obtained.

[0038] Example 2 In this embodiment, the functional nano-silicon dioxide inorganic powder material and the porous fiber base material are placed in an oven and fully dried at 120°C for 1 hour. The fiberglass felt is cut into 150mm*150mm using a fiber cutter, and then 35wt.% of the nano-silicon dioxide inorganic powder material is weighed, and the nano-silicon dioxide powder is evenly dispersed on the porous fiber base material; the porous fiber base material loaded with the nano-silicon dioxide inorganic powder material is placed in an alternating electric field environment, wherein the voltage of the alternating electric field is set to 20kV and the frequency is set to 500Hz. Very low frequency electromagnetic waves are generated by the alternating electric field, and the sample is ensured to be fully processed, and finally the functional fiber composite material sample 2 is obtained.

[0039] Example 3 In this embodiment, the functional nano-ruthenium oxide inorganic powder material is placed in an oven and dried at 120°C for 1 hour to ensure that the material is fully dried. The titanium fiber felt is cut into 30mm*10mm using a fiber cutter, and then 0.1wt.% of the nano-ruthenium oxide inorganic powder material is weighed and evenly dispersed on the porous fiber base material; the porous fiber base material loaded with the nano-ruthenium oxide inorganic powder material is placed in an alternating electric field environment, wherein the voltage of the alternating electric field is set to 20kV and the frequency is set to 1kHz. Very low frequency electromagnetic waves are generated by the alternating electric field, and the sample is ensured to be fully processed, and finally the functional fiber composite material sample three is obtained.

[0040] Example 4 In this embodiment, the functional nano iron oxide material is placed in an oven and dried at 120°C for 1 hour to ensure that the material is fully dried. The carbon fiber felt is cut into 40mm*20mm using a fiber cutter, and then the nano iron oxide material with a loading amount of 35wt.% is weighed, and the nano iron oxide material is evenly dispersed on the porous carbon fiber base material; the porous fiber base material loaded with the nano iron oxide material is placed in an alternating electric field environment, wherein the voltage of the alternating electric field is set to 10kV and the frequency is set to 500Hz. Very low frequency electromagnetic waves are generated by the alternating electric field, and the sample is ensured to be fully processed, and finally the functional fiber composite material sample 4 is obtained.

[0041] Example 5 In this embodiment, the functional nano-alumina material is placed in an oven and dried at 120°C for 1 hour to ensure that the material is fully dried. The carbon fiber felt is cut into 100mm*100mm using a fiber cutter, and then the nano-alumina material required for a loading amount of 70wt.% is weighed, and the nano-alumina material is evenly dispersed on the porous carbon fiber base material; the porous fiber base material loaded with the nano-alumina material is placed in an alternating electric field environment, wherein the voltage of the alternating electric field is set to 10kV and the frequency is set to 2kHz. Very low frequency electromagnetic waves are generated by the alternating electric field, and the sample is ensured to be fully processed, and finally the functional fiber composite material sample five is obtained.

[0042] The fiber composite material sample 1-2 obtained in Example 1-2 was subjected to an X-ray diffraction test, and the test results are shown in Figure 2 .from Figure 2 It can be seen that the sample prepared in Example 1 has a diffuse broad peak at 18°~30°, which is a typical amorphous SiO 2 This is because the main components of the base material glass fiber mat are amorphous silicon dioxide structures, and the remaining peaks are SiC. The sample prepared in Example 2 has a broad and diffuse scattering peak at 18°~30°, which is a typical amorphous SiO 2 This diffuse broad peak is because the amorphous structure lacks long-range ordered lattice arrangement, resulting in its diffraction pattern not having sharp diffraction peaks like crystalline materials. This shows that the main components of the glass fiber and the added silica that constitute the glass fiber mat are amorphous silica structures.

[0043] The fiber composite material sample 1-2 obtained in Example 1-2 was subjected to a scanning electron microscope (SEM), and the test results are shown in Figure 3 Through the SEM image, it can be clearly observed that the inorganic non-metallic powder is tightly wrapped on the fiber surface of the glass fiber mat. The filling of inorganic powder reduces the gaps between the fibers and enhances the overall density of the material.

[0044] The fiber composite material sample 1 obtained in Example 1 was tested for its wave absorbing performance on a vector network analyzer using a waveguide method. The test results are shown in Figure 6 .Depend on Figure 6 (a) It can be seen that the silicon carbide glass fiber composite material has stable dielectric properties within the X-band, and both the real and imaginary parts of the complex dielectric constant remain stable. Compared with the real part, the imaginary part of the silicon carbide glass fiber composite material is lower. Figure 6 (b) It can be seen that the real part of the complex dielectric constant of silicon carbide glass fiber composite material is relatively large, and the imaginary part is relatively small, so the dielectric loss of the material is also relatively small. Figure 6 (c) It can be seen that the reflectivity of the sample varies from 0 to -0.15dB, and the minimum reflectivity is -0.11dB. The overall loss capacity of the material to electromagnetic waves can also be measured by the attenuation constant α. Figure 6 (d) It can be seen that at 8 GHz, the α value is low, and the signal propagation attenuation is slow. As the frequency increases to 11 GHz, α gradually increases, the material's ability to absorb electromagnetic waves increases in this frequency band, and the signal attenuation also accelerates. From 11 GHz to 12 GHz, α gradually decreases, and the ability to absorb electromagnetic waves in this frequency band is weakened. At 11 GHz, the material has the strongest ability to absorb electromagnetic waves.

[0045] The fiber composite material sample 2 obtained in Example 2 was subjected to a thermal insulation performance test. The thermal insulation performance test process was to heat the preheater to 650°C and maintain it for 5 minutes before placing the sample on a heating table for testing. After the test time of 20 minutes, the temperature curves of the cold and hot surfaces of the composite material were obtained, and the thermal insulation performance of the material was evaluated by the time-temperature curve. The test results are shown in Figure 7 .Depend on Figure 7 It can be seen that the hot end temperature is stable between 680 and 690 °C. As the heat transfer proceeds, the hot end temperature of the glass fiber felt before the addition of silica rises rapidly. When the heat transfer lasts for 20 minutes, the hot end temperature of the material reaches 441.4 °C. Compared with the glass fiber felt before the addition of silica, the hot end temperature of sample 2 rises slowly. When the heat transfer lasts for 20 minutes, the hot end temperature of sample 2 is 358 °C, which is 83.4 °C lower than the hot end temperature of the material before the addition of white carbon black. The addition of silica reduces the thermal conductivity of the material and improves the thermal insulation performance of the material. Figure 3 It can be seen that the silica particles fill the pores between the fibers of the glass fiber mat. On the one hand, the silica particles reduce the porosity inside the glass fiber mat, thereby increasing the density of the material. On the other hand, the presence of silica particles makes the heat transfer path in the glass fiber mat more complicated, especially in the solid phase transfer process. At the same time, the silica particles also hinder the gas phase heat transfer in the glass fiber mat, reducing the overall thermal conductivity of the material.

[0046] In summary, the prepared functional fiber composite materials can be applied to acoustic systems and thermal management systems.

[0047] A core-shell structure functional fiber composite material based on a frequency-controllable alternating electric field, characterized in that it is composed of functional inorganic non-metallic powder and porous fiber material; the functional inorganic non-metallic powder material includes one or more of nano-silicon dioxide, aluminum oxide, silicon carbide, iron oxide, and phase change material.

[0048] The embodiments described with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention. The embodiments should not be regarded as limiting the present invention, but any improvements made based on the spirit of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a core-shell structure functional fiber composite material based on a frequency-controllable alternating electric field, characterized in that: The following steps are included: Step 1: Evenly dispersing the inorganic non-metallic powder material on the surface of a porous fiber base material having a suitable pore structure; Step 2: Place the sample in an alternating electric field environment and apply the alternating electric field for 10 seconds to 10 minutes to achieve a close bond between the functional inorganic non-metallic powder material and the fiber substrate, and finally obtain a functional fiber composite material.

2. The method for preparing a core-shell structure functional fiber composite material based on a frequency-controllable alternating electric field according to claim 1, characterized in that: The inorganic non-metallic powder material includes one or more of nano silicon dioxide, aluminum oxide, silicon carbide, iron oxide, and phase change material.

3. The method for preparing a core-shell structure functional fiber composite material based on a frequency-controllable alternating electric field according to claim 1, characterized in that: In the step 2, the operating frequency of the alternating electric field is 50-1 kHz, and the alternating voltage ranges from 5000 to 20000 volts.

4. The method for preparing a core-shell structure functional fiber composite material based on a frequency-controllable alternating electric field according to claim 1, characterized in that: The functional inorganic non-metallic powder material is loaded in the porous fiber substrate pore structure, and the loading amount thereof is 0.1 wt.% to 70 wt.%.

5. The method for preparing a core-shell structure functional fiber composite material based on a frequency-controllable alternating electric field according to claim 1, characterized in that: The particle size range of the functional inorganic non-metallic powder material is within 1 mm.

6. The method for preparing a core-shell structure functional fiber composite material based on a frequency-controllable alternating electric field according to claim 5, characterized in that: The particle size range of the functional inorganic non-metallic powder material is within 300 microns.

7. The method for preparing a core-shell structure functional fiber composite material based on a frequency-controllable alternating electric field according to claim 1, characterized in that: The porous fiber base material is fiber felt.

8. A method for preparing a core-shell structure functional fiber composite material based on a frequency-controllable alternating electric field according to any one of claims 1 to 8, characterized in that: The density of the porous fiber base material is 20-1000 kg / m 3 ,.

9. A method for preparing a core-shell structure functional fiber composite material based on a frequency-controllable alternating electric field according to any one of claims 1 to 8, characterized in that: The thickness of the porous fiber base material is 0.1-20 mm.

10. A core-shell structure functional fiber composite material based on a frequency-controllable alternating electric field, characterized in that: It is composed of functional inorganic non-metallic powder and porous fiber material; the functional inorganic non-metallic powder material includes one or more of nano silicon dioxide, aluminum oxide, silicon carbide, iron oxide, and phase change material.

Citation Information

Patent Citations

  • Preparation method of composite silicon dioxide aerogel felt

    CN110922095A

  • Aerogel waterproof heat insulation felt and manufacturing method thereof

    CN115257087A

  • Aerogel filled carbon fiber composite material and preparation method thereof

    CN117777666A

  • Preparation method of pre-modified hydrophobic silica aerogel composite fiber felt

    CN118186753A

  • Cleaning device for cleaning air-ionizing part of electrode

    CN103608987A